Ventilators and Ventilatory Modalities - Pavone, Martino; Verrillo, Elisabetta; Onofri, Alessandro; Caggiano, Serena; Cutrera, Renato (Frontiers in Pediatrics, 2020)
Non-invasive ventilation is increasingly used in children for acute and chronic respiratory failure. Ventilators available for clinical use have different levels of complexity, and clinicians need to know in detail their characteristics, setting variables, and performances. A wide range of ventilators are currently used in non-invasive ventilation including bi-level ventilators, intermediate ventilators, and critical care ventilators. Simple or advanced continuous positive airway pressure devices are also available. Differences between ventilators may have implications on the development of asynchronies and air leaks and may be associated with discomfort and poor patient tolerance. Although pressure-targeted (controlled) mode is preferable in children because of barotrauma concerns, volume-targeted (controlled) ventilators are also available. Pressure support ventilation represents the most used non-invasive ventilation mode, as it is more physiological. The newest ventilators allow the clinicians to use the hybrid modes that combine the advantages of volume- and pressure-targeted (controlled) ventilation while limiting their drawbacks. The use of in-built software may help clinicians to optimize the ventilator setting as well as to objectively monitor patient adherence to the treatment. The present review aims to help the clinician with the choice of the ventilator and its ventilation modalities to ensure a successful non-invasive ventilation program.